A curadoria em um repositório institucional: uma análise sob a ótica do ciclo de vida dos dados (CVD-CI) de Sant’Ana - Albuquerque, Morgana Ramos (2018)
The current exponential growth in data production is result of the development and use of Information and Communication Technologies. The phenomenon, known as Big Data, promotes a production of data in a scale never seen before brings to surface the challenge to mantain and preserve these digital objects. In this context the digital curatorship proposes actions to take care of and protect data in digital systems offering conditions for its use and future access. In this regard the curatorship acts upon the steps of a life cycle with the objective of guaranteeing that the necessary actions for management and preservation to be properly implemented. Within the digital environments, the warehouse is presented as an information system with framework capable of storing and disseminating the data in an efficient way. In view of that, the study achieved to identify the process of digital curatorship of academic documents produced by a Higher Education Institute from the standpoint of data lifespan of Sant’Ana(CVD-CI). Through the specific objectives, it was possible to verify the management (technology, processes and team) of academic documents of the chosen institution; verify the framework and planning of digital environments and analyse actions of the curatorship under the perspective of the lifespan steps chosen. The methodology used, of qualitative approach, consisted in a study case of management and preservation of digital documents produced in a Higher Education Institute located in Fortaleza, Ceará. The analysis' focus were the data and digital environment of the institution, in this way, as derived data were verified the steps of the Sant’Ana cycle regarding the final graduation works, dissertations and thesis, and the library management system and DSpace as environment. The data analyses presented the gathering, storage, recovery and disposal, led by the Sant’Ana lifespan, to identify that actions were taken by the institution or needed improvement. The results were based by the literature and presented suggestions for the management and preservation of the documents, as the necessity of an automatic collection for exemple. As conclusion the results obtaind presented solutions to improve the curatorship of digital academic documents in the institution, among them the creation of a digital contents policy.